Google style: os impactos do modelo organizacional flexível sobre os trabalhadores de uma empresa de TIC - Milhomem, Mariana Mundim (Universidade Federal de São Carlos, 2023)
From the 1970s onwards, the information technology revolution led to changes not only in the technological sphere, but also contributed to the configuration of new forms of social and economic relations. The emergence of a so-called “informational economy”, associated with a flexible accumulation regime, characterizes an era marked by commercial, technological and organizational innovation, with the restructuring of traditional industry. As a consequence of these paradigm changes, a less hierarchical and more creative work model was observed, with some freedoms and specific benefits. However, this transformation also brought with it a process of precarious work, with greater emphasis on flexibility, intensification of work and the introduction of new forms of control. These trends have contributed to reconfiguring the physical space of work, making the line between leisure and work increasingly blurred. In this sense, this research sought to understand, based on a qualitative analysis, how workers perceive and experience changes in flexible management forms inspired by Google's ideal model. In this way, a case study was carried out in a digital marketing agency in São Carlos, based on interviews based on a semi-structured script and applied to its workers, as well as visits to the company, which made it possible to draw up a profile of its workers and which their perceptions about this new management model, especially its impacts on their subjectivity and the management of the border between work and leisure.
Google style: the impacts of the flexible organizational model on workers in an ICT company
Keywords: trabalho flexível; economia informacional; gestão flexibilizada; modelo de gestão Google; flexible work; information economy; flexible management; Google management model; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS